Implementation of Chrysanthemum Post-Harvest Technology in Tomohon City to Extend Storage Time - Meivie Lintang; Olvie Tandi; Payung Layuk (Universitas Sembilanbelas November Kolaka, 2020)
Chrysanthemum (Dendranthema grandiflora) is an ornamental plant that has high economic value, including flowers that are in great demand at domestic or abroad. As cut flowers, chrysanthemums are used for decoration and flower arrangements at weddings, and for opening new offices. The quality of cut flowers depends on the appearance and durability of freshness. Flowers with prime quality have a higher sale value compared to low-quality cut flowers. To maintain the quality of prime cut flowers still need to be implemented several treatments, especially when the flowers are ready to harvest to the consumers. The handling of post-harvest chrysanthemums is an important factor that is inseparable from the stages of cultivation and greatly influences the selling value and added value that will be obtained by farmers and traders. The use of pulsing and holding liquid during display will extend the chrysanthemum vase life. By implementing post-harvest chrysanthemums in accordance with handling procedures (SOP), chrysanthemums will be obtained that can meet quality standards and can provide added value for farmers and flower traders